What is a world? : on postcolonial literature as world literature - Cheah, Pheng (Online access with subscription: Duke University Press., 2016)
In What Is a World? Pheng Cheah draws on accounts of the world as a temporal process from Hegel, Marx, Heidegger, Arendt, and Derrida, and analyzes several postcolonial novels to articulate a normative theory of world literature's capacity to open up new possibilities for remaking the world.